Produk, Promosi, Pengetahuan dan Minat Mahasiswa Berinvestasi Syariah - Rudianto, Nur Ahmad Ricky; Abdani, Fadlil (Budgeting: Jurnal Akuntansi Syariah, 2025)
This study aims to determine the effect of products, promotions, and knowledge on students’ interest in investing in sharia. This study is a quantitative study with primary data and survey method. Respondents in this study were students at the Faculty of Economics and Business, Bangka Belitung University and the Faculty of Sharia and Islamic Economics, IAIN Syaikh Abdurrahman Siddik Bangka Belitung. The results showed that the type of product with a sig value of 0.00 is smaller than 0.05 so it is significant, meaning the type of product influences students' interest in investing in sharia. The significance value of promotion is 0.00 is smaller than 0.05 so it is significant, meaning promotions influence students' interest in investing in sharia. The sig value of knowledge is 0.426 greater than 0.05 so it is not significant, meaning knowledge does not influence students’ interest in investing in sharia. For simultaneous testing, the sig value of 0.00 is smaller than 0.05 so it is significant, meaning products, promotions, and knowledge influence students' interest in investing in sharia. The results of this study explain that the more investment product options and the more promotions about sharia investments, the more it will increase students' interest in investing in sharia. Meanwhile, knowledge about sharia investment turns out to have no effect on students' decisions to invest in sharia.